Políticas públicas para a juventude em tempos de globalização: uma construção possível? - Rocha, Rosli Souza da (2016)
This work searches a comprehensive understanding of effort, to the paths explored in recent years in Brazil in the construction of social policies for young people, taking into account the context of neoliberal policies and these constructions were able to support and answers youth issues. For this was made a contextualization of the impacts of capitalism at the stage of neoliberal globalization front the problems faced by youth, a historical contextualization of the Brazilian government's actions in relation to the care policies to this group, as well as description and analysis of the programs of the Federal Government allocated thereto. Because of the breadth of the subject, the time frame will be made from 1990 to 2013. In 1990 there is the adoption of the Statute of the Child and Adolescent, ECA, a fact that marks the beginning of the rules of the first actions intended exclusively for youth to the 2013 when it adopted the Statute of Youth, considered a landmark of the current National Policy for Youth.